Antimycobacterial activity of lichen substances - Honda, N. K.; Pavan, Fernando Rogério [UNESP]; Coelho, R. G.; de Andrade Leite, S. R. [UNESP]; Micheletti, A. C.; Lopes, T. I. B.; Misutsu, M. Y.; Beatriz, A.; Brum, R. L.; Leite, Clarice Queico Fujimura [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
We describe here the extraction and identification of several classes of phenolic compounds from the lichens Parmotrema dilatatum (Vain.) Hale, Parmotrema tinctorum (Nyl.) Hale, Pseudoparmelia sphaerospora (Nyl.) Hale and Usnea subcavata (Motyka) and determined their anti-tubercular activity. The depsides (atranorin, diffractaic and lecanoric acids), depsidones (protocetraric, salazinic, hypostictic and norstictic acids), xanthones (lichexanthone and secalonic acid), and usnic acid, as well seven orsellinic acid esters, five salazinic acid 8',9'-O-alkyl derivatives and four lichexanthone derivatives, were evaluated for their activity against Mycobacterium tuberculosis. Diffractaic acid was the most active compound (MIC value 15.6 mu g/ml, 41.6 mu M), followed by norstictic acid (MIC value 62.5 mu g/ml, 168 mu M) and usnic acid (MIC value 62.5 mu g/ml, 182 mu M). Hypostictic acid (MIC value 94.0 mu g/ml, 251 mu M) and protocetraric acid (MIC value 125 mu g/ml, 334 mu M) showed moderate inhibitory activity. The other compounds showed lower inhibitory activity on the growth of M. tuberculosis, varying from MIC values of 250 to 1370 mu M. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Mycobacterium tuberculosis; Lichens; Phenolic products derivatives; Tuberculostatic activity; Diffractaic acid